A influência da constituição morfológica da forma verbal na ausência de concordância em Português (Revista de Estudos da Linguagem, 1995)
ln this paper I analyse the influence ofthe morphological constitution ofthe verbal form onthe absence ofagreement between the verb and the NP subject of 3pp (third person of plural) in the colloquial Brazilian Portuguese. According to the results this absence is significantly more ftequent in the "regular" verbs (falalfalam, comei comem, fazlfazem, etc.) than in the other verbs (i.e. the ''non-regular" verbs). The central claim is that these results are due to the peculiar behavior ofthe ''regular'' verbs where lack ofagreement is the result of the interaction between variable processes - a morphosyntactic synchronic nde and some phonological diachronic processes.